BRASIL FRENTE À ESCASSEZ DE ÁGUA - Andréia de Menezes Olivo; Hamilton Mitsugu Ishiki (Universidade do Oeste Paulista, 2014)
The water is a vital resource to human and this shortage was resulted by rapid and unplanned population growth that contributes to reduce its offer, especially due to the water pollution caused by the human. Thinking about it , this revision have with objective discusses the water environmental value, the causes and consequences of its scarcity, as well as the problems that affect the water quality and consequently the man life. It also aims to expose the impacts of their scarcity and what might be the consequences of anthropogenic action and disregard for water. For this, was performad a research bibliographic descriptive and analytical in the current situation this resource in Brasil and the world, guided in books, scientific articles and documentaries, seeking to demonstrate the importance of water to the ecosystem, the problematic and the impacts of it scarcity for society.